Targeted vaccination with meningococcal polysaccharide vaccine in one district of the Czech Republic - Kriz, P; Vlckova, J; Bobak, M (Epidemiology and infection, 1995)
Vaccination against Neisseria meningitidis is not part of routine immunization schemes in any country; instead, targeted vaccination of groups at the highest risk is recommended during outbreaks and epidemics. After a long period of sporadic occurrence of meningococcal invasive disease, a new clone of Neisseria meningitidis C:2a:P1.2, ET-15/37, occurred in the Czech Republic, and caused local outbreaks in two neighbouring districts, Olomouc and Bruntal, in spring 1993. In Olomouc, a mass campaign was conducted during which 6191 students were vaccinated (5.6% of the total population of this locality and 96% of all students in the age group 15-19) within 2 weeks in June 1993. In Bruntal district, no such campaign was organized. In Olomouc, the incidence of invasive disease caused by Neisseria meningitidis C in the age group 10-24 decreased from 57 to 0 per 100,000 (P < 0.001) during the post-vaccination period (July 1993-August 1994), but no such decrease was observed in Bruntal. Although other factors can affect the frequency of disease, these results support the current recommendations of targeted vaccination in outbreaks of meningococcal disease.
Keywords: bakteriální vakcíny; lidé; mladiství; Adult; Meningitis, Meningococcal; Neisseria meningitidis; dítě; vakcinace; Incidence; meningokoková meningitida; Vaccination; Adolescent; Humans; Students; Disease Outbreaks; studenti; Česká republika; Meningococcal Vaccines; meningokokové vakcíny; Czech Republic; incidence; epidemický výskyt choroby; Bacterial Vaccines; Child; dospělí